1998
DOI: 10.1136/jnnp.65.3.374
|View full text |Cite
|
Sign up to set email alerts
|

Functional organisation of saccades and antisaccades in the frontal lobe in humans: a study with echo planar functional magnetic resonance imaging

Abstract: The cortical activation pattern of saccades and antisaccades (versus rest) in the frontal lobe was analysed using an echo planar imaging (EPI) technique in 10 healthy subjects. Statistical analysis of activity in the dorsolateral prefrontal cortex disclosed a significantly greater activation during antisaccades in this region than during saccades. On the other hand, activity in the frontal eye fields was not statistically diVerent in both tasks. These results confirm the important role of the dorsolateral pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 20 publications
3
39
0
1
Order By: Relevance
“…It has been argued that both of these processes depend on working memory resources mediated by the dorsolateral prefrontal cortex (DLPFC) (Roberts et al 1994;Stuyven et al 2000;Hutton et al 2002). This is supported by imaging studies which have found that, in addition to activation of the oculomotor circuitry described above, the DLPFC is activated during antisaccades but not pro-saccades performance (Sweeney et al 1996;Dorricchi et al 1997;Muri et al 1998;McDowell et al 2002) and evidence showing increased antisaccade errors following DLPFC damage (Guitton et al 1985;Pierrot-Deseilligny et al 1991;Fukushima et al 1994). Thus one hypothesis is that a signal from DLPFC to FEF activates an inhibitory mechanism within FEF, which results in suppression of a reflex pro-saccade and generation of an antisaccade (Munoz and Everling, 2004).…”
Section: Discussionmentioning
confidence: 54%
“…It has been argued that both of these processes depend on working memory resources mediated by the dorsolateral prefrontal cortex (DLPFC) (Roberts et al 1994;Stuyven et al 2000;Hutton et al 2002). This is supported by imaging studies which have found that, in addition to activation of the oculomotor circuitry described above, the DLPFC is activated during antisaccades but not pro-saccades performance (Sweeney et al 1996;Dorricchi et al 1997;Muri et al 1998;McDowell et al 2002) and evidence showing increased antisaccade errors following DLPFC damage (Guitton et al 1985;Pierrot-Deseilligny et al 1991;Fukushima et al 1994). Thus one hypothesis is that a signal from DLPFC to FEF activates an inhibitory mechanism within FEF, which results in suppression of a reflex pro-saccade and generation of an antisaccade (Munoz and Everling, 2004).…”
Section: Discussionmentioning
confidence: 54%
“…We did not observe any signiWcant activation in the SEF during saccadic eye movements. Activation in the SEF related to reXexive or voluntary saccade eye movements has been reported by some (Fox et al 1985;Darby et al 1996;Petit et al 1996;Law et al 1998;Luna et al 1998;Muri et al 1998;Berman et al 1999;Nobre et al 2000), but not by others (Anderson et al 1994;Mort et al 2003).…”
Section: Discussionmentioning
confidence: 94%
“…PET studies have shown activation during reXexive saccades in FEF (Anderson et al 1994;Sweeney et al 1996), PEF (Anderson et al 1994), cerebellum, striate cortex and posterior temporal cortex (Sweeney et al 1996). fMRI studies have also shown activation in FEF (Petit et al 1997;Luna et al 1998;Muri et al 1998; Berman et al Table 2 Areas of activation (voluntary saccades > Wxation) with cluster size, maximum t value within the cluster, MNI coordinates of the maximum t value, anatomic labels, percentage of cluster size and functional area All areas were thresholded at P < 0.05 with FDR (whole brain study) or at cluster level (P < 0.05) corrected for multiple comparisons (cerebellum study) and with a minimum cluster size of 10 voxels L left hemisphere, R right hemisphere, FEF frontal eye Welds, PEF parietal eye Welds, MT/V5 motion-sensitive area (MT/V5), PVA/V1 primary visual areas (V1) a The unassigned areas for each cluster are not listed in the Muri et al 1998;Berman et al 1999;Nobre et al 2000), and the cerebellum (Nobre et al 2000), as well as in SEF (Luna et al 1998;Berman et al 1999), the precuneus , the cingulate gyrus Nobre et al 2000), MT/V5, PVA/V1 and the midbrain. In general, subjects in these studies were asked to execute saccadic eye movement towards suddenly appearing peripheral targets.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used successfully to characterize development of the ability to voluntarily suppress prepotent responses throughout late childhood and adolescence (Fischer et al, 1997;Munoz et al, 1998). The brain systems subserving performance on the antisaccade task have been well-delineated in monkeys (Burman et al, 1997;Everling et al, 1999;Funahashi et al, 1993;Gottlieb et al, 1999;Schlag-Rey et al, 1997) and adult humans (Guitton et al, 1985;Sweeney et al, 1996;Muri et al, 1998;Doricchi et al, 1997;O'Driscoll et al, 1995). These areas include the frontal eye field (FEF), supplementary eye fields (SEF), dorsolateral prefrontal cortex (DLPFC), posterior parietal cortex, anterior cingulate cortex, basal ganglia, thalamus, and superior colliculus.…”
Section: Introductionmentioning
confidence: 99%